Reconciling Relations: Shifting Counselling Psychology to Address Truth and Reconciliation - Fellner, Karlee D.; Ansloos, Jeffrey; Ouellette, Nevada L.; Villebrun, Gwendolyn D. (Canadian Journal of Counselling and Psychotherapy, 2020)
In 2018, the Canadian Counselling Psychology Conference (CCPC) convened a working group to address how the field of counselling psychology ought to respond to the Truth and Reconciliation Commission of Canada. Attendees were asked to share their perspectives on reconciliation, current efforts toward reconciliation in counselling psychology, and recommendations for the future of counselling psychology in relation to reconciliation. The current paper documents the findings and implications of the working group, offering concrete suggestions for how researchers, educators, clinicians, and trainees in the field can support reconciliation in a good way, shifting counselling psychology to serve Indigenous people and communities better.